Опыт разведения домашних оленей на архипелаге Новая земля - Volzhanina, E. A.; Волжанина, Е. А. (Издательство Тюменского государственного университета, 2016)
This article encourages readers to take a look at the experience of domestic reindeer breeding on the islands of Novaya Zemlya, that was conducted in the first third of the 20th century. This example drew attention to the idea of artificial reindeer breeding, which is designed to emphasize an initiation of food base for population, and in particular, to compensate the loss of a significant reduction of a wild deer hunting. Domestic reindeer herding of the archipelago Novaya Zemlya existed less than 10 years – from 1928 to 1937, but it left an imprint on the development of hunting and fishing in island economy. On the one hand, it was reflected on genetic mixing of reindeer, that were brought from Kolguev island with wild individuals of the Novaya Zemlya, which is recognized as «geographical isolates». On the other hand, there is the statement that domestic reindeer on the Novaya Zemlya is Nenets traditional economy. The article draws on in-depth archival work. Рассмотрен опыт разведения домашних оленей на архипелаге Новая земля.